Análisis doctrinario, jurídico y comparado del tratamiento a los adolescentes víctimas de violencia sexual’ - Espinosa Hidalgo, Paulina Cecilia (2024)
The current curriculum integration research titled “Doctrinal, legal and comparative analysis of the treatment of adolescent victims of sexual violence'', aims to raise awareness on an alarming reality of high incidence in society, that could potentially lead to devastating physical and psychological consequences in the lives of adolescents. These consequences hold significant relevance in the legal sphere as they entail a violation of sexual and reproductive freedom, fundamental rights for the comprehensive development of teenagers. Therefore, it is utterly important to provide appropriate and comprehensive treatment that contributes to healing, recovery, and rebuilding their lives. deep This research’s target is to go deep into different doctrinal and legal perspectives surrounding the topic by analyzing current laws and policies in various countries. A specific treatment of adolescent victims could be established by comparing approaches adopted by different legal systems, strengths and weaknesses regarding, allowing for specific recommendations to enhance responses and protect their rights. In addition, it examines existing protocols and programs to provide support to adolescent victims in educational and health contexts, as well as prevention and awareness- raising policies implemented at the national and international levels. This will provide a comprehensive view of available measures and identify good practices that can be replicated in other contexts. The results obtained in this study reveal an understanding regarding the similarities and differences in the sexual violence treatment for adolescent victims of each country, as well as an analysis about the application of comprehensive strategies. This research employed materials and methods for its development, including interviews and surveys with legal professionals, whose results contributed to proposing proactive guidelines. In short, this thesis project focuses on evaluating existing recovering policies and mechanisms; and treatment provided to adolescent victims of sexual violence in Ecuador, comparing them with practices used in other countries.